Studying the effect of the genotypes of the prolactin gene (PRL) on the productive performance of Holstein cows - MAUJ S. Harbeya; ABDALLAH H. SALM (University of Thi-Qar Journal of agricultural research, 2021)
The study was conducted at Taj Al-Nahrain station in Al-Diwaniyah Governorate, which is 200 km from the center of Dhi Qar Governorate. For the period from 10/15/2021 to 4/15/2021, 85 Holstein cows imported from Germany were used in this experiment, and they were selected from among 700 cows in the station, all of which are in the third production cycle. As for the laboratory part of the study, it was conducted in the laboratories of the Department of Life Sciences at the College of Science / Dhi Qar University for the purpose of separating the genetic material (DNA), conducting polymerase chain reaction and electrophoresis, and identifying genetic mutations in the studied genetic segment on the prolactin gene, The animals in the station were fed according to the season and year in terms of the availability of feed and the percentage of costs involved in raising cows, as well as depending on the general state of cow productivity. But in general, it is provided with green fodder, which includes yoghurt, barley, corn stalks, and a percentage of both dry feed (hay and hay) and concentrated feed (barley, bran and cake) according to what is available from them, as well as limestone and table salt. The data on milk production were collected from the station records, where the milk production was recorded weekly for the morning circuit and the evening circuit by the station, and the milk components were analyzed in the Abu Ghraib Dairy Company / Research and Development Division by a Milk Analyzer, and 3 ml of blood was collected from a vein The udder of each cow was given by medical syringes with a capacity of 5 ml, suitable for the size of the animal’s vein, and placed in collection tubes containing an anticoagulant substance (K2 EDTA) and transferred in a cooler box for freezing at a temperature of -18°C until the time of extraction. From the results obtained from this study, it can be concluded that the mutation C83T changed the code of the amino acid histidine to the amino acid Tyrosine, which had a significant effect on the characteristics of daily and total milk production, while the mutation G168C changed the amino acid arginine to the amino acid Proline, which was significantly reflected on the traits of persistence. In milk production, the length of the milk season and the proportion of milk protein, most of the average traits for cows in the third season of production appeared higher than the general averages compared to other studies, and most of the simple correlation coefficients between the study traits were high and significant.